The Size of Tympanic Membrane Perforation Area Positively Correlates with The Hearing Threshold of Chronic Suppurative Otitis Media Patient - Nindya Shinta Rumastika; Syahda Nabilla Aristawidya; Zahrah Febianti (Faculty of Medicine, University of Jember, 2022)
Chronic suppurative otitis media (CSOM) or what is known as congek by the local communities, is an ear disease that often occurs in developing countries. Chronic middle ear infection is accompanied by perforation of the tympanic membrane and fluid in the form of watery, clear, thick, even pus that comes out continuously or occurs for 2 months or more. The purpose of this riset was to analyze the relationship between the area of tympanic membrane perforation and hearing threshold value of CSOM patients at RSU Kaliwates Jember. This research is an observational analytic study with a cross sectional approach using secondary data recorded in the medical records of Kaliwates Hospital for 2019-2020. Data analysis using IBM SPSS Pearson test. This study used 15 ears from 12 CSOM patients obtained by a total sampling methode according to inclusion and exclusion criteria. From the analysis, it was found that there was a positive relationship between the area of the tympanic membrane perforation and hearing threshold value (p-value = 0.004) and had a strong degree of correlation (correlation coefficient value was 0.654).